2011
DOI: 10.1007/s00704-011-0550-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term precipitation variability in the Ionian Islands, Greece (Central Mediterranean): climatic signal analysis and future projections

Abstract: The present study examines the variability of the precipitation regime across the Ionian Islands complex, Greece (Central Mediterranean), for a period spanning more than one century. Significant negative long-term linear trends in the annual precipitation totals are observed, more pronounced in the southern parts of the studied area, while a climatic discontinuity possibly occurred during the 1970s, manifested first in the southern Ionian. Statistically significant nonlinear trends and subdecadal intermittent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…Precipitation trends were not significant, but a positive long-term tendency was observed in the amount of spring precipitation and a negative one in the summer precipitation. Autocorrelation peaks found at 7 years in the winter, spring and fire-season precipitation, are possibly associated with the 7-8-year oscillatory mode of NAO (Kalimeris et al 2012). Climatic signals in the 3.5-year band related to ENSO have been reported by many researchers.…”
Section: Discussionmentioning
confidence: 90%
“…Precipitation trends were not significant, but a positive long-term tendency was observed in the amount of spring precipitation and a negative one in the summer precipitation. Autocorrelation peaks found at 7 years in the winter, spring and fire-season precipitation, are possibly associated with the 7-8-year oscillatory mode of NAO (Kalimeris et al 2012). Climatic signals in the 3.5-year band related to ENSO have been reported by many researchers.…”
Section: Discussionmentioning
confidence: 90%
“…This is the main reason for the identification of significant breakpoints in the Spanish data but not in the Greek data. However, respective breaks in the mean air temperature time series over various regions in Greece in the early 1970s and middle 1990s (Nastos et al, 2011;Kolokythas and Argiriou, 2013) and in the precipitation time series between 1970 and 1980 (in the broader sense) (Pnevmatikos and Katsoulis, 2006;Feidas et al, 2007;Kalimeris et al, 2012) lead to the conclusion that an actual break in FWI series in the decade between 1970 and 1980 is also plausible. It should be noticed, however, that further testing is required in order to identify whether the breakpoints are artificial and due to exogenous variables or whether they actually indicate altering periods in the FWI values.…”
Section: Discussionmentioning
confidence: 99%
“…The annual number of fires and area burnt was strongly correlated with the maximum temperatures and summer heat waves. An evaluation of FWI performed recently using fire observations of a 15-year period for Greece confirmed that the index is capable of predicting fire occurrence (Karali et al, 2014). Additionally, Dimitrakapoulos et al (2011a) found that there was a positive correlation between the annual drought and fire occurrence in Greece during the years 1961-1997.…”
Section: Introductionmentioning
confidence: 88%
“…Similarly, the mean annual air temperature in Greece was found to exhibit cooling trends from early 50s to mid-70s, then stabilizing at low levels before increasing again after early 90s (Nastos et al, 2011). Regarding precipitation, there were some marked breaks between the period 1971-1978 in some weather stations in the Ionian islands (north-west Greece) indicating shifts in the time-series towards reduced precipitation amounts during the latter periods (Kalimeris et al, 2012). According to Feidas et al (2007) an approximation of the starting period of decreasing trend of the precipitation amounts in Greece is the decade between 1974 to 1984.…”
Section: Discussionmentioning
confidence: 89%